“HOUSING Frankfurt Wien Stockholm”: Exhibition of 1920s–1930s Housing Initiatives - Monterumisi, Chiara (2019)
Frankfurt, Vienna and Stockholm: three European cities which played a fundamental role in the housing policies implemented during the inter-war period. The research projects and teaching activity carried out at the EPFL in the Laboratory of Construction and Conservation focuses on this specific historic context. The experiences of these three cities with regard to housing are well documented from a historical viewpoint that, however, show many shortcomings with regards to the architectural analysis. The provided examples sum up simultaneously the social dynamics, the cultural milieu, as well as the adopted intentions and political programme. The exhibition aims at producing fresh knowledge of the three contributions to modern housing available to students, scholars, professors and architectural practitioners. The goal is to compare a selection of remarkable housing neighbourhoods through the different scales of the project, ranging from the relation with the city till the dwelling unit layout. The produced drawings and documents show the morphological and typological variety. Frankfurt, Vienna and Stockholm equally illustrate different ways of designing the collective space—that is the intermediary space in-between the communal and private – which is a crucial feature of the “living together”.